2021
DOI: 10.1177/08944393211025758
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, Challenges, and Social Impact of Health Care Providers’ Adoption of Social Media

Abstract: With the advent of telecommunication technologies and social media, many health care professionals are using social media to communicate with their patients and to promote health. However, the literature reveals a lacuna in our understanding of health care professionals’ perception of their behavioral intentions to use innovations. Using the Unified Technology Acceptance Framework (unified theory of acceptance and use of technology), in-depth interviews were conducted with 16 Australian health care experts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“… 32 , 44 , 45 , 46 It is suggested that Twitter can be used as a platform for patient education not only to promote mental health through online social support but can also help to ease the stigma of psychiatric disorders. 21 , 47 , 48 During the pandemic, it was found that the public was more dependent on social media to receive and share information with peers. 44 A previous literature review suggested that although the optimal balance of digital and conventional healthcare was still to be explored, social media has already become a ubiquitous and versatile tool in healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 32 , 44 , 45 , 46 It is suggested that Twitter can be used as a platform for patient education not only to promote mental health through online social support but can also help to ease the stigma of psychiatric disorders. 21 , 47 , 48 During the pandemic, it was found that the public was more dependent on social media to receive and share information with peers. 44 A previous literature review suggested that although the optimal balance of digital and conventional healthcare was still to be explored, social media has already become a ubiquitous and versatile tool in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…It is apparent that Twitter is being used as a platform to disseminate information associated with novel uses of antidepressants, with evidence shared within research communities and to the general public. 18 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, using social media could pose some challenges, including threatening privacy, the lack of control over the interactions such as interacting with unidentifiable peers, and the reliability of information presented (Househ et al, 2014; Khan & Loh, 2021; Moorhead et al, 2013b). Future intervention may include a moderator such as a nurse who can clarify information and promote confidence by using encrypted messaging for privacy.…”
Section: Discussionmentioning
confidence: 99%